The Effect Of Using Collaborative Learning Method On Students’ Writing Ability In Descriptive Text At The Tenth Grade Students Of SMAN 7 Mandau - Nur Insani Wulan Sari (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
The purpose of this study was to determine the significant effect of using collaborative learning method on students’ writing ability in descriptive text. The researcher used quasi-experimental research design with quantitative approach. The population of this study was 205 tenth grade students of SMAN 7 Mandau consisting of six classes. The researcher took two classes X1 and X2 as samples totaling 67 students, one class as an experimental class that was given treatment and one class as a control class that was not given treatment. Students were selected using cluster random sampling. To collect the data, the researcher used a written test. The results of significant differences in the post-test writing of experimental class students and post-test control classes can be seen from the results of the independent t-test from SPSS 27 showing that sig. (2-tailed) is less than 0.05 (0.000 <0.05). So, Ho is rejected and Ha is accepted. This meant that there was a significant difference in students’ writing ability between the experimental class that used the Collaborative Learning method and the control class that did not use the Collaborative Learning method.